An overview of recent progress in nanostructured carbon-based supercapacitor electrodes: From zero to bi-dimensional materials. (30th June 2022) - Kumar, Rajesh; Joanni, Ednan; Sahoo, Sumanta; Shim, Jae-Jin; Tan, Wai Kian; Matsuda, Atsunori; Singh, Rajesh K.
Abstract: The lack of higher performance energy storage has been widely acknowledged as a major factor hindering further developments in transportation, portable and wearable electronic devices, among other key applications. Although supercapacitors (SCs) have been known for more than fifty years, only recently these devices have been considered as promising candidates to fulfil this significant technology gap. Developments in nanotechnology and manufacturing techniques applied to high-performance advanced electrode materials have accelerated progress in this fast-moving field. In this comprehensive overview article, we systematically survey the current state of art on fabrication and the corresponding electrochemical performance of electrode materials for SCs. The text covers novel carbon nanomaterials having different dimensions, such as 0D-carbon quantum dots, 1D-carbon nanostructures (carbon nanotubes, carbon nanofibers, carbon nano yarns and their composites) as well as 2D-carbon materials (graphene, doped-graphene, graphene derivatives and their composites). Emerging fabrication technologies are also addressed, including conventional SCs, as well as asymmetric, flexible, micro, stretchable and wearable devices. Additionally, the drawbacks for each class of electrode material, the major challenges facing the current technologies, and some of the promising research directions in this field have also been discussed. Graphical abstract: Image 1